Habitat Fragmentation and Population Size of the Black and Gold Howler Monkey (Alouatta caraya) in a Semideciduous Forest in Northern Argentina - Zunino, Gabriel Eduardo (2007)
A population of black and gold howler monkeys (Alouatta caraya) living near the southern limit of its distribution in a semideciduous forest located in northern Argentina was studied in 2003 to evaluate the possible effects of habitat fragmentation - owing to logging - on its density and social organization within it. Aerial photographs taken in 1982, 1992, and 2001 were used to compare maps of vegetation. These maps were used to evaluate changes in the area covered by forest fragments. From March to June 2003, 10-day monthly surveys of howlers were made in each fragment. A total of 232 individual howlers were counted, belonging to 34 groups plus a solitary adult female. Groups ranged from 2 to 19 individuals (mean = 6.82, SD = 4.23), and 21% of the groups contained more than one adult male. Adults accounted for 55% of the individuals, immatures for 45%, and infants represented 13% of the total. Data obtained were compared with information available for the same population for 1982 and 1995. Results revealed no significant changes in the area of fragments, the crude and ecological density of howlers, and group composition. Group sizes and group composition of howlers suggest that the population remained stable over the past 22 years. The density, number of groups, and individuals appears not to be affected by fragmentation and logging, but crude density was low compared with other less-disturbed habitats. The status of the population remains uncertain owing to isolation, and because there are no protected areas to ensure its stability for the future.